Tungsten bronze type Ho-Zr co-doped strontium sodium niobate-based luminous energy storage ceramic material and preparation method thereof

By doping Ho3+ and Zr4+ in tungsten bronze ceramic materials and adjusting their crystal structure, the problem that ceramic materials in the prior art are difficult to have high energy storage density and luminous performance, and high-efficiency ceramic materials are achieved.

CN119822825APending Publication Date: 2025-04-15XIJING UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411958804.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

It is difficult to develop a ceramic material with high energy storage density and excellent luminescence performance in the prior art, especially in the multifunctional material combining energy storage and luminescence, and the research is relatively weak.

Method used

The crystal structure and functional characteristics of the material are adjusted by double doping Ho3+/Zr4+ in the A/B position of the Sr2Ag0.2Na0.8Nb4.8Sb0.2O15 system.

Benefits of technology

The high energy storage density and good luminous performance of ceramic materials were achieved, the energy storage density reached 2.54J/cm3, the energy storage efficiency was maintained at 86%, and it showed strong green light emission (544nm) under 460nm light excitation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119822825A_ABST
    Figure CN119822825A_ABST
Patent Text Reader

Abstract

The invention discloses a tungsten bronze type Ho-Zr co-doped strontium sodium niobate-based luminous energy storage ceramic material and a preparation method, the structural general formula of the ceramic material is (Sr < 2-x > Ho < x > Ag < 0.2 > Na < 0.8 >) (Nb < 4.8-x > Zr < x > Sb < 0.2 >) O < 15 >, and the value of x is 0.02-0.08. The tungsten bronze type Ho-Zr co-doped strontium sodium niobate-based luminous energy storage ceramic material is prepared through material preparation, ball milling, pre-sintering, secondary ball milling, sieving, tabletting and sintering; the preparation method is simple, low in cost, good in repeatability and high in yield, the obtained ceramic material has high energy storage density, when x is equal to 0.05, the breakdown electric field of the ceramic material reaches up to 300 kV / cm, and the effective energy storage density of the ceramic material is 2.54 J / cm < 3 >. In addition, the ceramic material provided by the invention also has good photoluminescence performance, and can emit strong green light at 544 nm under the excitation of 460 nm ultraviolet light.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramic materials, and relates to a tungsten bronze structured luminescent energy storage ceramic material, and specifically relates to a tungsten bronze type Ho-Zr co-doped sodium strontium niobate based luminescent energy storage ceramic material and a preparation method thereof. Background Art

[0002] In order to solve the energy crisis and environmental pollution problems, people have made great efforts to develop clean energy and high-power energy storage systems. Compared with batteries and electrochemical capacitors, dielectric capacitors have attracted much attention due to their good temperature stability, fast charge and discharge rates, ultra-high power density and excellent mechanical properties. However, the development trend of electronic devices is towards miniaturization, lightweight and functional integration. Single functional materials can no longer meet the actual needs. Therefore, many researchers have invested a lot of energy in multifunctional materials. For example, piezoelectric transparent materials, ferroelectric-elastic-magnetic materials, and energy storage transparent materials, etc., dual-parameter and three-parameter coupled multifunctional materials. Tungsten bronze compounds are an indispensable and important branch of the lead-free piezoelectric ferroelectric material system. Its general structural formula is (A1)2(A2)4C4(B1)2(B2)8O 30 Different metal cations selectively occupy non-equivalent crystallographic interstitial positions in A1, A2, B1, B2 and C positions 5 according to their radius and valence, thus giving them flexible and varied crystal structures and functional properties. However, there are few reports on multifunctional materials combining energy storage and luminescence. Therefore, it is of practical and strategic significance to develop a ceramic material with luminescence and energy storage properties. Summary of the invention

[0003] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a tungsten bronze type Ho-Zr co-doped sodium strontium niobate based ceramic material with high energy storage density and excellent luminescence performance and a preparation method, the preparation method has simple process, good repeatability and low cost.

[0004] In order to achieve the above object, the present invention adopts the following technical solutions:

[0005] A tungsten bronze type Ho-Zr co-doped sodium strontium niobate based luminescent energy storage ceramic material, the general structural formula is (Sr 2- x Ho x Ag 0.2 Na 0.8 )(Nb 4.8-x Zr x Sb 0.2 ) 15 , where the value of x is 0.02~0.08.

[0006] Preferably, the value of x is 0.05.

[0007] The present invention also protects a method for preparing the above-mentioned tungsten bronze type Ho-Zr co-doped sodium strontium niobate-based luminescent energy storage ceramic material, comprising the following steps:

[0008] Step 1: According to the stoichiometric ratio, weigh the powder raw materials of SrCO3, Ho2O3, Ag2O, Na2CO3, Nb2O5, Sb2O3 and ZrO2 respectively, put the weighed raw materials into a ball mill, and then dry and grind them to obtain a raw material mixture;

[0009] Step 2: Put the raw material mixture into an alumina crucible, and then put the crucible in a box furnace, pre-sinter at 1130-1170° C. for 5-7 hours, grind, ball-mill, dry, grind again, and then sieve to obtain pre-sintered powder;

[0010] Step 3: After the pre-sintered powder is pressed into a sheet, the muffle furnace is heated to 690-710°C at a rate of 4-9°C / min in an air atmosphere, and then heated to 1250-1300°C at a rate of 2-4°C / min, and kept warm for 3-5 hours. Finally, it is naturally cooled to room temperature to obtain a tungsten bronze type Ho-Zr co-doped strontium niobate-based ceramic material with high energy storage density and good luminescence performance.

[0011] Preferably, the ball milling in step 1 and step 2 is performed using zirconium balls as grinding balls and anhydrous ethanol as ball milling medium, and the mixture is fully mixed and ball milled for 16 to 20 hours.

[0012] Preferably, the grinding in step 1 and step 2 is performed by grinding in a mortar for 10 to 30 minutes.

[0013] Preferably, the drying in step 1 and step 2 is performed by placing the product in an oven at 70 to 90° C. for 20 to 24 hours.

[0014] Preferably, the sieving in step 2 is through a 180-mesh sieve.

[0015] Preferably, the pre-sintered powder tablets in step 3 are pressed into cylindrical green bodies using a powder tablet press, and then cold isostatically pressed at a pressure of 180 to 220 MPa for 4 to 6 minutes.

[0016] Compared with the prior art, the present invention has the following technical effects:

[0017] The present invention selects Sr2Ag 0.2 Na 0.8 Nb 4.8 Sb 0.2 O 15 The A / B position of the system is Ho 3+ / Zr 4+ Double doping, Ho3+ Entering the A position of the tungsten bronze structure is conducive to obtaining energy storage ceramic materials with luminescent properties; Zr 4+ The introduction of high band gap ions into the B position of tungsten bronze structure increases the resistivity and insulation performance of the sample, effectively reducing the generation of leakage current. 3+ / Zr 4+ The introduction of inhibits grain growth, reduces grain size and pore quantity, increases density of ceramics, and thus increases breakdown field strength of ceramics; in addition, heterovalent Ho 3+ / Zr 4+ The introduction of enhances the local disorder of the material. 1.95 Ho 0.05 Ag 0.2 Na 0.8 )(Nb 4.75 Zr 0.05 Sb 0.2 ) 15 The energy storage ceramic breakdown strength can reach 300kV / cm, the energy storage efficiency remains at 86%, and the energy storage density is 2.54J / cm 3 , and also has good photoluminescence performance, with strong green light emission at 544nm under 460nm light excitation;

[0018] The preparation method of the invention has simple process, good repeatability and low cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 XRD patterns of ceramic materials prepared in Examples 1 to 4 and Comparative Example 1;

[0020] Figure 2 The dielectric constant and dielectric loss diagram of the ceramic material prepared in Comparative Example 1 at different test frequencies;

[0021] Figure 3 The dielectric constant and dielectric loss diagram of the ceramic material prepared in Example 3 at different test frequencies;

[0022] Figure 4 The unipolar hysteresis loop diagram of the ceramic materials prepared in Examples 1 to 4 and Comparative Example 1 under the critical breakdown electric field;

[0023] Figure 5 A comparison chart of the effective energy storage density and energy storage efficiency of the ceramic materials prepared in Examples 1 to 4 and Comparative Example 1 under the critical breakdown electric field;

[0024] Figure 6 The emission spectra of the ceramic materials prepared in Examples 1 to 4 and Comparative Example 1 are shown. DETAILED DESCRIPTION

[0025] The specific contents of the present invention are further explained in detail below in conjunction with the examples. The reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art. The test methods in the following examples where specific experimental conditions are not specified are usually based on conventional experimental conditions. Unless otherwise specified, the reagents and raw materials used in the present invention can be obtained commercially.

[0026] Example 1

[0027] Step 1: According to (Sr 1.98 Ho 0.02 Ag 0.2 Na 0.8 )(Nb 4.78 Zr 0.02 Sb 0.2 ) 15 According to the stoichiometric ratio, 8.5276 g of SrCO3 with a purity of 99.95%, 0.1102 g of Ho2O3 with a purity of 99.99%, 1.2363 g of Na2CO3 with a purity of 99.99%, 0.6778 g of Ag2O with a purity of 99.7%, 18.5261 g of Nb2O5 with a purity of 99.99%, 0.8501 g of Sb2O3 with a purity of 99.99%, and 0.0719 g of ZrO2 with a purity of 99.99% were weighed respectively, put into a nylon jar, and milled for 20 h in a ball mill at a speed of 401 r / min using zirconium balls as grinding balls and anhydrous ethanol as ball milling media, dried at 80°C for 24 h, and ground in a mortar for 30 min to obtain a raw material mixture;

[0028] Step 2: Place the raw material mixture in an alumina crucible, compact it with an agate rod, cover it, place it in a resistance furnace, heat it to 1150°C at a heating rate of 3°C / min, keep it warm for 6 hours, cool it naturally to room temperature with the furnace, take it out of the furnace, grind it with a mortar for 30 minutes, and then perform secondary ball milling according to the method of step 1, ball milling for 20 hours, place it in a drying oven at 80°C for 24 hours, grind it with a mortar for another 10 minutes, and pass it through a 180-mesh sieve to obtain a pre-calcined powder;

[0029] Step 3: Place the pre-burned powder into a stainless steel mold with a diameter of 11.5 mm, press it into a cylindrical body with a thickness of 1.3 mm without pressure using a powder tablet press, place the cylindrical body into a cold isostatic press, and cold isostatic press for 5 minutes at a pressure of 200 MPa; place the cylindrical body on a zirconia zirconium plate, place the zirconia zirconium plate in an alumina closed sagger, heat it to 700°C at a heating rate of 5°C / min, and then heat it to 1270°C at a heating rate of 3°C / min, keep warm for 4 hours, and naturally cool it to room temperature with the furnace to obtain a tungsten bronze type Ho-Zr co-doped sodium strontium niobate-based luminescent energy storage ceramic material.

[0030] Example 2

[0031] Step 1: According to (Sr 1.97 Ho 0.03 Ag 0.2 Na 0.8 )(Nb 4.77 Zr 0.03 Sb 0.2 ) 15 According to the stoichiometric ratio, 8.4820 g of SrCO3 with a purity of 99.95%, 0.1652 g of Ho2O3 with a purity of 99.99%, 1.2360 g of Na2CO3 with a purity of 99.99%, 0.6776 g of Ag2O with a purity of 99.7%, 18.4817 g of Nb2O5 with a purity of 99.99%, 0.8499 g of Sb2O3 with a purity of 99.99%, and 0.1078 g of ZrO2 with a purity of 99.99% were weighed respectively, put into a nylon jar, and milled for 16 h in a ball mill at a speed of 401 r / min using zirconium balls as grinding balls and anhydrous ethanol as ball milling media, dried at 70°C for 22 h, and ground in a mortar for 10 min to obtain a raw material mixture;

[0032] Step 2: Place the raw material mixture in an alumina crucible, compact it with an agate rod, cover it, place it in a resistance furnace, heat it to 1130°C at a heating rate of 3°C / min, keep it warm for 7 hours, cool it naturally to room temperature with the furnace, take it out of the furnace, grind it with a mortar for 20 minutes, and then perform secondary ball milling according to the method of step 1, ball milling for 16 hours, place it in a drying oven at 70°C for 22 hours, grind it with a mortar for another 15 minutes, and pass it through a 180-mesh sieve to obtain a pre-calcined powder;

[0033] Step 3: Place the pre-burned powder into a stainless steel mold with a diameter of 11.5 mm, press it into a cylindrical body with a thickness of 1.3 mm without pressure using a powder tablet press, place the cylindrical body into a cold isostatic press, and cold isostatic press for 6 minutes at a pressure of 180 MPa; place the cylindrical body on a zirconia zirconium plate, place the zirconia zirconium plate in an alumina closed sagger, heat it to 690°C at a heating rate of 4°C / min, and then heat it to 1250°C at a heating rate of 2°C / min, keep warm for 5 hours, and naturally cool it to room temperature with the furnace to obtain a tungsten bronze type Ho-Zr co-doped sodium strontium niobate-based luminescent energy storage ceramic material.

[0034] Example 3

[0035] Step 1: According to (Sr 1.95 Ho 0.05 Ag 0.2 Na 0.8 )(Nb 4.75 Zr 0.05 Sb 0.2 )15 According to the stoichiometric ratio, 8.3907 g of SrCO3 with a purity of 99.95%, 0.2752 g of Ho2O3 with a purity of 99.99%, 1.2352 g of Na2CO3 with a purity of 99.99%, 0.6771 g of Ag2O with a purity of 99.7%, 18.3929 g of Nb2O5 with a purity of 99.99%, 0.8493 g of Sb2O3 with a purity of 99.99%, and 0.1795 g of ZrO2 with a purity of 99.99% were weighed respectively, put into a nylon jar, and milled for 16 h in a ball mill at a speed of 401 r / min using zirconium balls as grinding balls and anhydrous ethanol as ball milling media, dried at 90°C for 20 h, and ground in a mortar for 20 min to obtain a raw material mixture;

[0036] Step 2: Place the raw material mixture in an alumina crucible, compact it with an agate rod, cover it, place it in a resistance furnace, heat it to 1170°C at a heating rate of 3°C / min, keep it warm for 5 hours, cool it naturally to room temperature with the furnace, take it out of the furnace, grind it with a mortar for 10 minutes, and then perform secondary ball milling according to the method of step 1, ball milling for 18 hours, place it in a drying oven at 90°C for 20 hours, grind it with a mortar for another 30 minutes, and pass it through a 180-mesh sieve to obtain a pre-calcined powder;

[0037] Step three, place the pre-burned powder into a stainless steel mold with a diameter of 11.5 mm, press it into a cylindrical body with a thickness of 1.3 mm without pressure using a powder tablet press, place the cylindrical body into a cold isostatic press, and cold isostatic press for 4 minutes at a pressure of 220 MPa; place the cylindrical body on a zirconia zirconium plate, place the zirconia zirconium plate in an alumina closed sagger, heat it to 710°C at a heating rate of 9°C / min, and then heat it to 1300°C at a heating rate of 4°C / min, keep warm for 3 hours, and naturally cool it to room temperature with the furnace to obtain a tungsten bronze type Ho-Zr co-doped sodium strontium niobate-based luminescent energy storage ceramic material.

[0038] Example 4

[0039] In step 1 of this embodiment, according to (Sr 1.92 Ho 0.08 Ag 0.2 Na 0.8 )(Nb 4.72 Zr 0.08 Sb 0.2 ) 15According to the stoichiometric ratio, 8.2540g of SrCO3 with a purity of 99.95%, 0.4400g of Ho2O3 with a purity of 99.99%, 1.2341g of Na2CO3 with a purity of 99.99%, 0.6765g of Ag2O with a purity of 99.7%, 18.2599g of Nb2O5 with a purity of 99.99%, 0.8486g of Sb2O3 with a purity of 99.99%, and 0.2869g of ZrO2 with a purity of 99.99% were weighed respectively and put into a nylon can. The other steps were the same as those in Example 1 to obtain a tungsten bronze type Ho-Zr co-doped sodium strontium niobate based luminescent energy storage ceramic material.

[0040] Comparative Example 1

[0041] According to Sr2Ag 0.2 Na 0.8 Nb 4.8 Sb 0.2 O 15 The stoichiometric ratio is 8.6190 g of SrCO3 with a purity of 99.95%, 0.6782 g of Ag2O with a purity of 99.7%, 1.2371 g of Na2CO3 with a purity of 99.99%, 18.6150 g of Nb2O5 with a purity of 99.99%, and 0.8506 g of Sb2O3 with a purity of 99.99%. The other steps are the same as those in Example 1 to obtain a tungsten bronze type sodium silver strontium niobate antimonate lead-free ceramic material.

[0042] The tungsten bronze type Ho-Zr co-doped sodium strontium niobate-based luminescent energy storage ceramic material prepared in the above examples 1 to 4 and the tungsten bronze type sodium strontium niobate-based energy storage ceramic material prepared in comparative example 1, the ceramic sheet thickness is polished to 150μm, and gold electrodes are plated on the upper and lower surfaces of the ceramic using an ion sputtering instrument. The conditions of ion sputtering include: the target material is a gold target, the current is 15mA, and the time is 200ms. Then, its ferroelectric properties are tested at room temperature and a frequency of 10Hz. The SmartLab9 type X-ray diffractometer produced by Japan Rigaku Co., Ltd., the DMS-2000 series high and low temperature dielectric impedance thermometer produced by China Bailibo Co., Ltd., the ferroelectric tester produced by Radiant Co., Ltd. of the United States, and the F-4600 type fluorescence spectrophotometer are used to test the fluorescence performance excitation spectrum and emission spectrum, and the phase structure and performance are characterized and tested, and the relevant performance parameters are calculated by the following formula:

[0043] Dielectric constant ε r :ε r =4Ct / (πε0d)

[0044] Effective energy storage density W rec :

[0045] Total energy storage density Wtotal :

[0046] Where: C is the capacitance, t is the thickness of the ceramic sheet, ε0 is the vacuum dielectric constant, d is the diameter of the ceramic sheet, P m is the maximum polarization intensity, P r is the residual polarization intensity, E is the electric field intensity, and the results are shown in Figures 1 to 6 .

[0047] Figure 1 XRD patterns of the ceramic materials prepared in Examples 1 to 4 and Comparative Example 1; Figure 1 It can be seen that the ceramic materials prepared in Examples 1 to 4 and Comparative Example 1 all present a tungsten bronze structure as a main phase, accompanied by a small amount of Na0.5Sr0.25NbO3 as a second phase.

[0048] Figure 2 The dielectric constant and dielectric loss diagram of the ceramic material prepared in Comparative Example 1 at different test frequencies; Figure 3 The dielectric constant and dielectric loss diagram of the ceramic material prepared in Example 3 at different test frequencies; Figures 2-3 It can be seen that compared with the Curie temperature of the ceramic material prepared in Comparative Example 1, the Curie temperature of the ceramic material prepared in Example 3 is obviously moved toward room temperature, that is, the relaxor ferroelectric phase is adjusted to near room temperature.

[0049] Figure 4 1 is a unipolar hysteresis loop diagram of the ceramic materials prepared in Examples 1 to 4 and Comparative Example 1 under the critical breakdown electric field; Figure 4 It can be seen that with the 3+ / Zr 4+ With the increase of doping amount, the breakdown field strength of the ceramic material prepared in Example 3 is significantly improved, from 230 kV / cm in Comparative Example 1 to 300 kV / cm. The increase of breakdown field strength leads to a significant increase of energy storage density.

[0050] Figure 5 A comparison chart of the effective energy storage density and energy storage efficiency of the ceramic materials prepared in Examples 1 to 4 and Comparative Example 1 under the critical breakdown electric field; Figure 5 It can be seen that the effective energy storage density of the ceramic material prepared in Comparative Example 1 is 1.77 J / cm 3 , the energy storage efficiency is 82.4%, after Ho 3+ / Zr 4+ After dual doping at the A / B positions, the energy storage density and energy storage efficiency of the ceramic materials prepared in Examples 1 to 4 are significantly improved, and the energy storage density is about 1.85 to 2.54 J / cm 3 , the energy storage efficiency is about 85.8-90.8%, especially when Ho 3+ / Zr +When the doping amount is 0.05, the effective energy storage density of the ceramic is as high as 2.54J / cm 3 , the energy storage efficiency remains at 85.9%.

[0051] Figure 6 The emission spectra of the ceramic materials prepared in Examples 1 to 4 and Comparative Example 1 are shown in FIG. Figure 6 It can be seen that the ceramic materials prepared in Examples 1 to 4 can emit strong green light at 544nm under the excitation of 460nm ultraviolet light. It can be seen that the tungsten bronze structure ceramic material of the present invention has both high energy storage density and photoluminescence properties, and is expected to become a candidate material for energy storage-luminescence ceramic capacitors.

[0052] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A tungsten bronze type Ho-Zr co-doped sodium strontium niobate based luminescent energy storage ceramic material, characterized in that: The general structural formula is (Sr 2-x Ho x Ag 0.2 Na 0.8 )(Nb 4.8-x Zr x Sb 0.2 ) 15 , where the value of x is 0.02~0.

08.

2. The tungsten bronze type Ho-Zr co-doped sodium strontium niobate based luminescent energy storage ceramic material according to claim 1, characterized in that: The value of x is 0.

05.

3. A method for preparing the tungsten bronze type Ho-Zr co-doped sodium strontium niobate-based luminescent energy storage ceramic material as claimed in claim 1 or 2, characterized in that: The following steps are involved: Step 1: According to the stoichiometric ratio, weigh the powder raw materials of SrCO3, Ho2O3, Ag2O, Na2CO3, Nb2O5, Sb2O3 and ZrO2 respectively, put the weighed raw materials into a ball mill, and then dry and grind them to obtain a raw material mixture; Step 2: Put the raw material mixture into an alumina crucible, and then put the crucible in a box furnace, pre-sinter at 1130-1170° C. for 5-7 hours, grind, ball-mill, dry, grind again, and then sieve to obtain pre-sintered powder; Step 3: After the pre-sintered powder is pressed into a sheet, the muffle furnace is heated to 690-710°C at a rate of 4-9°C / min in an air atmosphere, and then heated to 1250-1300°C at a rate of 2-4°C / min, and kept warm for 3-5 hours. Finally, it is naturally cooled to room temperature to obtain a tungsten bronze type Ho-Zr co-doped strontium niobate-based ceramic material with high energy storage density and good luminescence performance.

4. The method for preparing the tungsten bronze type Ho-Zr co-doped sodium strontium niobate-based luminescent energy storage ceramic material according to claim 3, characterized in that: The ball milling described in step 1 and step 2 uses zirconium balls as grinding balls and anhydrous ethanol as ball milling medium, and the mixture is fully mixed and ball milled for 16 to 20 hours.

5. The method for preparing the tungsten bronze type Ho-Zr co-doped sodium strontium niobate based luminescent energy storage ceramic material according to claim 3, characterized in that: The drying in step 1 and step 2 is performed by placing the product in an oven at 70 to 90° C. for 20 to 24 hours.

6. The method for preparing the tungsten bronze type Ho-Zr co-doped sodium strontium niobate based luminescent energy storage ceramic material according to claim 3, characterized in that: The grinding described in step 1 and step 2 is performed by grinding in a mortar for 10 to 30 minutes.

7. The method for preparing the tungsten bronze type Ho-Zr co-doped sodium strontium niobate based luminescent energy storage ceramic material according to claim 3, characterized in that: The sieving described in step 2 is through a 180-mesh sieve.

8. The method for preparing the tungsten bronze type Ho-Zr co-doped sodium strontium niobate based luminescent energy storage ceramic material as claimed in claim 3, characterized in that: The pre-sintered powder tablets described in step 3 are pressed into cylindrical green bodies using a powder tablet press, and then cold isostatically pressed at a pressure of 180 to 220 MPa for 4 to 6 minutes.